2016
DOI: 10.1186/s40201-016-0260-0
|View full text |Cite
|
Sign up to set email alerts
|

A new bioindicator, shell of Trachycardium lacunosum, and sediment samples to monitors metals (Al, Zn, Fe, Mn, Ni, V, Co, Cr and Cu) in marine environment: The Persian Gulf as a case

Abstract: BackgroundThe present work was designed to detect heavy metal contents of Al, Zn, Fe, Mn, Ni, V, Co, Cr and Cu in sediments and shells of the Trachycardium lacunosum collected in polluted and unpolluted areas along the Persian Gulf.MethodsThe samples were taken from surface sediments (0-10 cm) and shells of Trachycardium lacunosum in two separated areas (polluted and unpolluted) in northern part of the Persian Gulf, Asaluyeh Bay, during summer 2013. The prepared samples were analyzed by inductively coupled pla… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 22 publications
(8 citation statements)
references
References 32 publications
(33 reference statements)
0
8
0
Order By: Relevance
“…However, current studies on bivalve shells persistence and importance are few and in most cases have focused in the marine environment (Cadeé, 1999), being the freshwater ecosystems seldom investigated. Additionally, most of the studies regarding shells use were performed in laboratory, in which the shells were used as sensitive tools, to detect chemical contamination of the water due to their capacity to retain different heavy metals over different time periods (Bellotto and Miekeley, 2007;Nuñez et al, 2012;Karbasdehi et al, 2016), and to evaluated the influence of acidification on shell dissolution (Bednaršek et al, 2012;Bausch et al, 2018), whereas field studies are rare (but see Strayer and Malcom, 2007;Ilarri et al, 2015a). Overall, the findings of the present study suggest that the bivalve shell decays vary among species, shell size, water flow and season.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, current studies on bivalve shells persistence and importance are few and in most cases have focused in the marine environment (Cadeé, 1999), being the freshwater ecosystems seldom investigated. Additionally, most of the studies regarding shells use were performed in laboratory, in which the shells were used as sensitive tools, to detect chemical contamination of the water due to their capacity to retain different heavy metals over different time periods (Bellotto and Miekeley, 2007;Nuñez et al, 2012;Karbasdehi et al, 2016), and to evaluated the influence of acidification on shell dissolution (Bednaršek et al, 2012;Bausch et al, 2018), whereas field studies are rare (but see Strayer and Malcom, 2007;Ilarri et al, 2015a). Overall, the findings of the present study suggest that the bivalve shell decays vary among species, shell size, water flow and season.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have also showed that bivalve shells can be used as indicator tools to monitor pollution and environmental changes, with the use of shells to detect the presence of several heavy metals in the environment (e.g. Al, Zn, Mn, Ni, Co, Cr and others;Nuñez et al, 2012;Karbasdehi et al, 2016), and also to assess changes in water pH (Marshall et al, 2018). Therefore, it is important to understand the mechanisms behind the shell decays of different species subjected to different environmental conditions in order to better comprehend the persistence and importance of bivalve shells in the ecosystems.…”
Section: Introductionmentioning
confidence: 99%
“…The time of water turnover in the basin is between 3 and 5 years and shows that pollutants likely to reside in the Persian Gulf for a significant time [2] , this has caused the north parts of the Persian Gulf to be much more influenced by contaminations [1] . Also, the former studies in the northern part of the Persian Gulf showed that these areas are affected by pollution [3] , [4] , [5] , [6] , [7] .
Fig.
…”
Section: Experimental Design Materials and Methodsmentioning
confidence: 98%
“…The mean concentrations of Cr in a variety of environmental and biological samples from the PGA were measured previously such as sediment (34.2 mg/kg. dry weight) [17]; zooplankton (0.05 µg/g) [26], shell (0.07 µg/g dw) [21], school children's' toenail (0.68 µg/L) [27], and mother and cord blood (7.08 and 6 µg/L, respectively) samples [5]. The nonnatural sources of Cr are coal and petroleum combustion waste from industries and domestics [55] that may in uence the levels of Cr in the PGA.…”
Section: Chromiummentioning
confidence: 99%
“…In addition to petrochemical and re neries complexes, a variety of other industries are also activating in Asaluyeh area that release a large amount of pollutants such as MLs in the surrounding environment and consequent harmful effects on human health [16]. Previous studies have ever been measured MLs levels in the environmental (sediment, air, street dust, ballast water, land ll leachates, and drinking water) [17][18][19][20][21][22][23][24][25] and biological (blood, toenail, sh, bivalve, and zooplankton) [5,6,[26][27][28][29][30][31] samples which have been attributed to the industrial activities in this region. Considering differences in the physiological condition of body among infants and adults, infants are more at health risk because of exposure to the environmental pollutants such as MLs.…”
Section: Introductionmentioning
confidence: 99%